Atypical sarcoidosis masquerading as neutropenia - Chaudhary, P.; Gopaluni, S.; Sanyal, et al., S. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2010)
Sarcoidosis is a systemic granulomatous disease of unknown etiology. Gastrointestinal involvement in sarcoidosis is rare and so are its hematological manifestations.We report an unusual case of sarcoidosis with isolated gastric involvement and concomitant B12 and iron deficiency, leucopenia and severe neutropenia. The diagnosis of GI tract sarcoidosis is difficult and other causes of GI tract granulomas should be excluded. Patients can have unusual manifestations like B12 deficiency and one should be aware of this possibility. Careful follow-up and frequent reevaluation of the patient may be a sound strategy in equivocal cases with unusual presentation.